The theological reflection on the divine in the African context: a possible basis for dialogue with Islam - Namukoa, Edward Wanyama (University of the Free State, 1998)
𝑬𝒏𝒈𝒍𝒊𝒔𝒉 The countries of Africa are experiencing important changes and development forms a major part of their political agenda. It is a period of economic awakening. This Renaissance of Africa is impossible to achieve without a new social order. This new social order is one that goes beyond sectional and ethnic hatred. This also implies a need for religious tolerance based on an acceptable concept understood equally by all religions and ethnic groups of Africa. In this thesis, the researcher sought to contribute to religious tolerance by looking at similarities and differences between the conceptions of the Divine held by the major religious traditions of Africa, viz. African traditional religion, Christianity and Islam. The thesis also explored the possibility of employing the conception of the Divine as a unifying factor and a possible basis for dialogue between religious communities in a multi-religious society. The investigation articulated the following three basic convictions which are central to the study: (a) The concept of the Divine in the African context is a complex one. (b) Christian theology in Africa has relevance for the ecumenical church. (c) Islam, like Christianity, also suffers from a religious ethnocentrism. In Chapter 1 attention was devoted to the problem and scope of the study, the conceptualisation of the problem, and the purpose and relevance of the study. The chapter contains a historical survey of African traditional religion, Christian Mission and the Islamic Da'wah in Africa. Lastly the researcher spelled out his personal stance as regards the subject under discussion and concluded with a discussion of African traditional religion, Christianity and Islam in Kenya. In Chapter 2 attention was devoted to the theological views on the Divine. This took the form of a general definition followed by specific attention to the way in which the concept is understood from the African, Christian and Islamic points of view. Attention was paid to the way in which these religions understand the attributes of God and the names of God and to how these views may contribute towards preparing the stage for dialogue. The African conception of the Divine has been misunderstood by Western writers, especially by the missionaries who initially had a pre-conceived notion of Africans and their understanding of God. The researcher discussed these views critically and concluded that Africans, like the Jews, believed in one God and that their concept of the Divine was evolving from simple to complex in a similar way as Yahweh of Israel and Allah of the Arabs also evolved from simple to complex up to the level at which the concept comes to us in the Bible and the Qur'an. In Chapter 3 the respective attitudes of African traditional religion, Christianity and Islam towards the Divine were explored. Emphasis was laid on the African Christians who take the gospel to their fellow Africans and who can therefore be regarded as missionaries among their own people. The Muslim attitude towards Allah and the Da'wah was also discussed. In Chapter 4 the theological views of the three religions on Monotheism, the Trinity and Predestination were explored. The findings revealed that the religions differ in this regard. The differences are more pronounced between Christianity and Islam. It was argued that, in order to achieve a religious symbiosis, the differences should be left to the adherents of the respective religions while emphasis should be laid on the concept of the Divine which is understood in a similar fashion in these religions. This could serve to effect a working togetherness in a multi-religious society. In Chapter 5 attention was devoted to the condition of sin. Sin was discussed as the major reason for the separation between man and the Divine. The views of the three religions on sin and the resulting strained relationship with the Divine were investigated .. The researcher believes that sin is the main cause of religious animosity between the adherents of these religions in Africa and specifically in Kenya. The remedy lies in looking to the Divine for a complete restoration and the possibility of dialogue. The question of salvation was investigated in Chapter 6. In discussing the theology of salvation in the African traditional Religion, Christianity and Islam attention was devoted to the way in which the theology of salvation relates to the perception of the Divine in these religions. The differences between the ways in which Christianity and Islam understand of salvation were discussed critically and the responses of each of the religions were articulated. Chapter 7 contains a few concluding remarks and a way forward was discussed. It was stressed that a social order based on the concept of religious tolerance is necessary in a multi-religious society. It is possible for people of different religions to work together under the umbrella of the concept of the Divine. Religious animosity is unnecessary in the 21st century and beyond, and quite untenable if Africa is to be developmentally conscious. There are common areas where African traditional religion, Christianity and Islam agree - especially with regard to the concept of the . Divine. This should be emphasised in order to promote peace; yet the individual religious differences should be respected as such. Attention was also devoted to the Christian witness in a multi-religious society and it was pointed out that Christians should learn to listen to other religions in order to be understood and accepted in their witness to the Gospel of the Lord Jesus Christ. ___________________________________________________________________

𝑨𝒇𝒓𝒊𝒌𝒂𝒂𝒏𝒔 Die lande in Afrika ondergaan tans belangrike veranderings en ontwikkeling speel 'n .groot rol speel in hulle politieke agenda. Die Afrika-renaissance is egter onmoontlik sonder 'n nuwe sosiale orde wat verder strek as faksies en etniese haat. Dit impliseer godsdienstige verdraagsaamheid gebaseer op 'n aanvaarbare konsep wat deur alle godsdienste en etniese groepe in Afrika eenders verstaan word. In hierdie proefskrif het die navorser gepoog om 'n bydrae tot godsdienstige verdraagsaamheid te lewer deur te kyk na ooreenkomste en verskille tussen die begrip van die Goddelike in die vernaamste godsdienstige tradisies van Afrika, nl. die tradisionele Afrika-godsdienste, die Christendom en Islam. Die proefskrif ondersoek ook die moontlikheid om die begrip van die Goddelike as 'n verenigende faktor en 'n moontlike basis vir dialoog in 'n multi-godsdienstigegemeenskap te behou. Die ondersoek artikuleer die volgende drie basiese begrippe wat sentraal in die studie staan: (a) Die begrip van die Goddelike in die Afrika-konteks is kompleks. (b) Christelike teologie in Afrika is relevant vir die ekumeniese kerk. (c) Islam, soos die Christendom, vertoon en gaan gebuk onder godsdienstige etnosentrisme. In hoofstuk 1 word aandag gewy aan die probleem en omvang van die studie, die konseptualisering van die probleem, asook die doel en die relevansie van die studie. Die hoofstuk bevat 'n histories oorsig van die Afrika- tradisionele godsdienste, Christelike Sending en die Islamitiese Da'wah in Afrika. Dit word gevolg deur 'n uiteensetting van die navorser se persoonlike standpunt ten opsigte van die onderwerp van bespreking, en eindig met 'n bespreking van die Afrika- tradisionele godsdiens, die Christendom en Islam in Kenia. In hoofstuk 2 word die teologiese sienings van die Goddelike bespreek. Daar word begin met 'n algemene definisie, gevolg deur spesifieke aandag aan die wyse waarop die konsep van die Goddelike vanuit die Afrika-oogpunt, asook dié van die Christendom en Islam verstaan word. Aandag is gewy aan die wyse waarop die drie godsdienste die eienskappe van God en die name van God verstaan en hoe hierdie sieninge tot dialoog kan bydra. Die Afrika-sienswyse van die Goddelike is deur Westerse skrywers misverstaan, en veral deur die sendelinge wat aanvanklik voorafopgestelde idees oor Afrikane en hulle begrip van God gehad het. Hierdie sienswyses word krities beoordeel en die gevolgtrekking is dat Afrikane, net soos die Jode, net in een God geglo het en dat hulle konsep van die Goddelike besig was om .te ontwikkel van die eenvoudige tot die komplekse, soortgelyk aan die wyse waarop Yahweh van Israel en Allah van die Arabiere ook van eenvoudige na komplekse begrippe ontwikkel het tot op die vlak waar die konsepte in die Bybel en die Koran tot ons kom. In hoofstuk 3 word die houding van die Afrika- tradisionele godsdiens, die Christendom en Islam teenoor die Goddelike ondersoek. Die rol van Afrika-Christene wat die evangelie na hulle mede-Afrikane uitdra en wat dus in hierdie verband as sendelinge onder hulle eie mense gereken kan word, is beklemtoon. Die Moslem-houding teenoor Allah en die Da'wah is ook bespreek. In hoofstuk 4 word die teologiese sieninge van die drie godsdienste oor monoteisme, die Drieëenheid en predestinasie bespreek. Die bevindinge toon dat die drie godsdiense in dié verband verskil. Die verskille is die grootste tussen die Christendom en die Islam. Daar is aangevoer dat vir 'n godsdienstige simbiose die verskille aan die aanhangers van die verskillende godsdienste oorgelaat behoort te word, terwyl klem gelê behoort te word op die konsep van die Goddelike wat deur die drie godsdienste eenders. verstaan word. Dit sou kon help om 'n werkende samehorigheid in 'n multi-godsdienstige samelewing te vestig. In hoofstuk 5 word aandag gegee aan die toestande van sonde. Sonde is bespreek as die hoofrede vir die verwydering tussen die mens en God. Die sieninge van die drie godsdienste oor sonde en die gevolglike versteurde verhouding met die Goddelike is ondersoek. Die navorser glo dat sonde die vernaamste oorsaak is van godsdienstige vyandigheid tussen van hierdie godsdienste in Afrika en spesifiek in Kenia. Die oplossing lê daarin om na die Goddelike te kyk vir 'n algehele herstel en dialoog. Die kwessie van heil word in hoofstuk 6 ondersoek. In die bespreking van die teologie van heil in die Afrika- tradisionele godsdiens, die Christendom en Islam is aandag gewy aan hoe hierdie teologie van heil die siening van die Goddelike in hierdie godsdienste beïnvloed. Die verskille tussen die wyse waarop die Christendom en Islam heil beskou, is krities bespreek en die reaksies van elk van die godsdienste is uitgespel. Hoofstuk 7 bevat enkele slotopmerkings en die weg vorentoe word bespreek. Die feit .dat 'n sosiale orde gebaseer op die konsep van godsdienstige verdraagsaamheid noodsaaklik is in 'n multi-godsdienstige samelewing is benadruk. Dit is moontlik vir mense van verskillende godsdienstige oortuigings om saam te werk onder die sambreel van die konsep van die Goddelike. Godsdienstige vyandigheid is onnodig in die 21ste eeu en heeltemalonhoudbaar indien Afrika ontwikkelingsbewus wil wees. Daar is gemeenskaplike gebiede waar die Afrika- tradisionele godsdienste, Christendom en Islam saamstem, veral ten opsigte van die konsep van die Goddelike. Dit behoort beklemtoon te word om vrede te bevorder, terwyl die individuele godsdientige verskille nogtans gerespekteer moet word. Aandag is ook gewy aan die Christelike getuienis in 'n multi-godsdienstige gemeeenskap en daar is daarop gewys dat Christene behoort te leer om na ander godsdienste te luister ten einde verstaan en aanvaar te word in hulle getuienis vir die evangelie van die Here Jesus Christus. ___________________________________________________________________
Thesis (Ph.D. (Missiology))--University of the Free State, 1998
Keywords: Christianity and other religions -- Relations; Religions -- Relations; Islam -- Relations -- Christianity